2020
DOI: 10.1016/j.chemosphere.2020.127312
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitro aryl hydrocarbon receptor-mediated activity of atmospheric particulate matter at an urban, agricultural and industrial site in North Africa (Bizerte, Tunisia)

Abstract: As recognized risk factor to pose a health threat to humans and wildlife globally, atmospheric particulate matter (PM) were collected from a North African coastal city (Bizerte, Tunisia) for one year, and were characterized for their chemical compositions, including mercury (Hg PM), as well as organic contaminants (polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), organochlorine pesticides (OCPs)), organic carbon (OC) and organic nitrogen (ON), determined in a previous study. Then, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 106 publications
0
4
0
Order By: Relevance
“…PM 10 samples collected between January 2015 and February 2016 at an urban site at Zouaghi, in the south of Constantine, showed that PM concentrations exceeded the WHO’s 24-h guideline value (50 µg m −3 ), linking such levels to resuspended dust and Saharan dust [ 64 ]. In Tunisia, the analysis of PM 10 constituents revealed the anthropogenic and natural sources of PM, derived from traffic emissions, heavy industries, biomass burning, mechanic and electronic factories, and agricultural activities gathered with meteorological conditions [ 65 ]. In Egypt, a study in the residential-industrial area Shubra El-Kheima in the north of Greater Cairo revealed that fine aerosol particle concentrations, collected during the period from October 2010 to May 2011, exceed the WHO annual Air Quality Standard levels.…”
Section: Resultsmentioning
confidence: 99%
“…PM 10 samples collected between January 2015 and February 2016 at an urban site at Zouaghi, in the south of Constantine, showed that PM concentrations exceeded the WHO’s 24-h guideline value (50 µg m −3 ), linking such levels to resuspended dust and Saharan dust [ 64 ]. In Tunisia, the analysis of PM 10 constituents revealed the anthropogenic and natural sources of PM, derived from traffic emissions, heavy industries, biomass burning, mechanic and electronic factories, and agricultural activities gathered with meteorological conditions [ 65 ]. In Egypt, a study in the residential-industrial area Shubra El-Kheima in the north of Greater Cairo revealed that fine aerosol particle concentrations, collected during the period from October 2010 to May 2011, exceed the WHO annual Air Quality Standard levels.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the concentration of 16 US EPA priority PAHs in PM 2.5 of Xi'an between November 15 and December 23, 2019 (the heating season), were analyzed. It was worth noting that the Acenaphthene (Ace) concentration in Xi'an was significantly higher than that in South Korea, Thailand, or the United States and even higher than that in other regions of China (Baek et al, 2020; Barhoumi et al, 2020; Dejchanchaiwong et al, 2020; Han et al, 2019; Khadhar et al, 2010). However, the other 15 kinds of PAHs have no significant difference as compared with these in other regions in China.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same fate can happen in MPs suspended in the atmosphere. Indeed, some POPs formed during the combustion process, such as polychlorinated dibenzodioxin and dibenzofurans, have been already detected in atmospheric PM [139]. In the atmosphere, MPs could be exposed to POPs but the adsorption is dependent on the time at which plastic particles are suspended.…”
Section: Contaminants Associated With Mp-npsmentioning
confidence: 99%